2014
DOI: 10.1111/ipd.12105
|View full text |Cite
|
Sign up to set email alerts
|

Association between developmental defects of enamel and early childhood caries: a cross‐sectional study

Abstract: The presence of ECC was associated with the occurrence of DDE in the primary dentition. Place of residence and monthly household income (socioeconomic indicators) and oral hygiene (behavioural factor) exerted an influence on the occurrence of ECC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
2
15
1
7
Order By: Relevance
“…Demarcated opacities were the most common type of DDE observed in the present study (11.5%), similarly to previous studies . A Brazilian study involving preschool children showed a slightly higher prevalence of demarcated opacities; however, that study involved children who were older than those in our study, different that used in our research. Other studies, however, reported a higher frequency of diffuse opacities .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Demarcated opacities were the most common type of DDE observed in the present study (11.5%), similarly to previous studies . A Brazilian study involving preschool children showed a slightly higher prevalence of demarcated opacities; however, that study involved children who were older than those in our study, different that used in our research. Other studies, however, reported a higher frequency of diffuse opacities .…”
Section: Discussionsupporting
confidence: 88%
“…According to this study, the overall prevalence of DDE in the primary teeth of children aged 24‐36 months was 13.1%. Worldwide, the prevalence of DDE in the primary dentition ranges from 3.9% to 81.3% . A birth cohort study in Brazil that followed up children to the age of 54 months revealed that 81.3% of the participants had at least one tooth affected by DDE .…”
Section: Discussionmentioning
confidence: 99%
“…3 Dental caries exerts a negative impact on the quality of life of both the child and the family, 2 and is considered a public health problem. The etiology of dental caries in childhood is associated with eating habits, 4,5 irregular tooth brushing 6,7 and socioeconomic indicators. 8 Children from economically vulnerable families have a higher…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies suggest that malnutrition episodes may increase susceptibility to caries due to defects in enamel development (hypoplasia) or alterations in the salivary glands [10]. Hypoplastic enamel is associated with the occurrence of early childhood caries [9]. In addition, malnourished children have lower buffering capacity and secretion rates of saliva, lower secretion rates of calcium and protein, and compromised immunological factors when compared to well-nourished children [19].…”
Section: Introductionmentioning
confidence: 99%